Shear Behaviour Of Perforated Cold-Formed Steel Section - Lee, Kenth Zheng (Universiti Sains Malaysia, 2017)
This dissertation presents a numerical study on the shear behaviour of steel framing system using perforated section. The unstable cost of steel causing cost to construct housing become unstable thus resulting in other choices of materials for construction. Perforated steel section has lower volume of steel, which cause the weight to decrease and cheaper in construction. However, perforation in steel will decrease shear resistance of steel framing system. The objective of this study is to investigate the shear behaviour of perforated steel section comparing to unperforated section in steel framing system. Perforated steel sections have lower volume of steel material as a result of perforated area. Critical shear loading from common steel framing system is obtained using Staad Pro software according to Eurocode Standard. The shear loading then transferred to model in LUSAS to perform finite element analysis. The results obtained were compared to the steel section without perforation. Eigenvalue analysis was performed and the results were compared by using eigenvalue as structure capacity. Optimal steel section for shear behaviour was determined from the results. The perforated sections were compared with unperforated section for shear capacity and percentage of volume reduction. Perforation steel section with 8 diamond openings was selected with percentage of shear buckling capacity difference from unperforated section about 33.02% and 48.18% with circle openings.